Tuna and tuna products: a review of the nutrition, processing, safety, and future prospects - Yi-Li, Tan; Juhari, Nurul Hanisah; Jambari, Nuzul Noorahya; Rozzamri, Ashari; Mahmud Ab Rashid, Nor-Khaizura; Ismail-Fitry, Mohammad Rashedi (Springer, 2025)
Tuna, part of the Scombridae family, are globally renowned teleost fish valued for their nutritional richness, particularly in protein and healthy fats. Tuna is popular in various cuisines, from sashimi to canned products. However, the industry faces challenges. Histamine fish poisoning, mercury contamination, and ciguatoxins pose significant health risks. Technological advancements in thermal and nonthermal processing aim to preserve tuna’s nutritional qualities while addressing safety concerns. Despite progress, these innovations must ensure consumer safety. This review gathers insights into current processing methods and health risks for tuna and tuna products’ sustainability. Balancing innovation, health concerns, and environmental impact is vital. The future of the tuna industry depends on overcoming these challenges and providing safe and nutritious products.